Different Patterns of Hearing Loss among Tinnitus Patients: A Latent Class Analysis of a Large Sample - Langguth, Berthold; Landgrebe, Michael; Schlee, Winfried; Schecklmann, Martin; Vielsmeier, Veronika; Steffens, Thomas; Staudinger, Susanne; Frick, Hannah; Frick, Ulrich (Frontiers in Neurology, 2017)
Background: The heterogeneity of tinnitus is a major challenge for tinnitus research. Even if a complex interaction of many factors is involved in the etiology of tinnitus, hearing loss has been identified as the most relevant etiologic factor. Here we used a data-driven approach to identify patterns of hearing function in a large sample of tinnitus patients presenting in a tinnitus clinic. Methods: Data from 2838 patients presenting at the Tinnitus Center of the University Regensburg between 2007 and 2014 have been analysed. Standard audiometric data were frequency-wise categorized in four categories (a: normal hearing (0-20 dB HL); b: moderate hearing loss (25 dB-50 dB HL; representing outer hair cell loss); c: severe hearing loss (>50 dB HL; representing outer and inner hair cell loss); d: no data available) and entered in a latent class analysis, a statistical method to find subtypes of cases in multivariate categorical data. To validate the clinical relevance of the identified latent classes they were compared with respect to clinical and demographic characteristics of their members. Results: The classification algorithm identified eight distinct latent classes with an excellent separation. Patient classes differed with respect to demographic (e.g. age, gender) and clinical characteristics (e.g. tinnitus location, tinnitus severity, gradual or abrupt onset etc.). Discussion: Our results demonstrate that data-driven categorization of hearing function seems to be a promising approach for profiling tinnitus patients, as it revealed distinct subtypes that reflect prototypic forms of hearing loss and that differ in several relevant clinical characteristics.